Independent contributions of fMRI familiarity and novelty effects to recognition memory and their stability across the adult lifespan - de Chastelaine, Marianne (Neuroimage, 2017)
The impact of age on the neural correlates of familiarity-driven recognition memory has received relatively little attention. Here, the relationships between age, the neural correlates of familiarity, and memory performance were investigated using an associative recognition test in young, middle-aged and older participants. Test items comprised studied, rearranged (items studied on different trials) and new word pairs. fMRI ‘familiarity effects’ were operationalized as greater activity for studied test pairs incorrectly identified as ‘rearranged’ than for correctly rejected new pairs. The reverse contrast was employed to identify ‘novelty’ effects. Estimates of familiarity strength were slightly but significantly lower for the older relative to the younger group. With the exception ofoneregion indorsal medial prefrontal cortex, fMRI familiarity effects (which were identified in medial and lateral parietal cortex, dorsal medial and left lateral prefrontal cortex, and bilateral caudate among other regions) did not differ significantly with age. Age-invariant ‘novelty effects’ were identified in the anterior hippocampus and the perirhinal cortex. When entered into the same regression model, familiarity and novelty effects independently predicted familiarity strength across participants, suggesting that the two classes of memory effect reflect functionally distinct mnemonic processes. It is concluded that the neural correlates of familiarity-based memory judgments, and their relationship with familiarity strength, are largely stable across much of the healthy adult lifespan.